Zmanjševanje potrošnje plastičnih vrečk - Šljivić, Marko (Javna uprava, 2021)
Plastic bags are one of the most popular products in the world, but their irresponsible consumption has resulted in many consequences. For this purpose, the European Union adopted Directive No. 2015/720 on reducing the consumption of light plastic carrier bags, which was transposed into Slovenian legal order by amending the Decree on the Management of Packaging and Waste Packaging and the Regulation on the Environmental Tax for Environmental Pollution due to the Production of Waste Packaging. Reducing the consumption of plastic bags was the first step in reducing the consumption of plastic products, as on the basis of Directive (EU) 2019/904 on reducing the environmental impact of certain plastic products, Decree on the Prohibition of Placing on the Market in the Republic of Slovenia of Certain Single-use Plastic Products and on the Labelling of Certain Plastic Products was recently adopted, which restricted the placing on the market in the Republic of Slovenia of certain single- use plastic products and made the labelling of certain other plastic products compulsory.
Keywords: bags; consumption; environment; European Union; odpadna embalaža; packaging handling; packaging waste; plastic; plastika; pravo EU; products; ravnanje z odpadki; Slovenia; Slovenija; varstvo okolja; vrečke